The role of parental income over the life cycle: A comparison of Sweden and the UK - Anders Björklund; Markus Jäntti; Martin Nybom (Institute for the Study of Labor (IZA), 2012)
Research on intergenerational income mobility has shown stronger persistence between parental and offspring's income in the UK than in Sweden. We use similar data sets for the two countries to explore whether these cross-national differences show up already early in offspring's life in outcomes such as birth weight, grades at the end of compulsory school at age 16, height during adolescence, and final educational attainment. We do indeed find significant country differences in the association between parental income and these outcomes, and the associations are stronger in the UK than in Sweden. Therefore, we continue to investigate whether these differentials are large enough to account for a substantial part of the difference in intergenerational persistence estimates. We then conclude that the country differences in the intergenerational associations in birth weight and height are too weak to account for hardly any fraction of the UK-Sweden difference in intergenerational income mobility. For the more traditional human-capital variables grades and final education, however, our results suggest that the country differences can account for a substantial part of the difference in income persistence.
Keywords: J24; 330; intergenerational mobility; birth weight; height; human capital; Intergenerational Mobility; Einkommen; Kinder; Gesundheit; Humankapital; Lebensverlauf; Vergleich; Großbritannien; Schweden